Sri Lanka : First Post-Program Monitoring Discussion. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY Context. Sri Lanka's economy has navigated recent market turbulence relatively well. Growth has remained solid, inflation is in mid-single digits, and the current account deficit has narrowed. From mid-May, the exchange rate came under pressure as market expectations of U.S. Federal Reserve tapering shifted, but Sri Lanka's experience was in line with that of other emerging markets. Since September, market pressures have eased. By some metrics, reserves remain on the low side, but were boosted in late-September by an external debt issue of a large state-owned bank. Monetary policy. Monetary policy has eased progressively since end-2012 as growth slowed, inflation fell, and private sector credit weakened. At the time of the mission, staff recommended keeping monetary policy on hold for the near term. However, policy rates were subsequently reduced, with the central bank citing continued low inflation and the opportunity to stimulate growth to a higher level in 2014. Fiscal policy. The authorities remain committed to fiscal consolidation and intend to meet their 2013 deficit target. However, the steady real decline in government revenue collection poses risks to needed medium-term fiscal consolidation. The 2014 budget offers an opportunity to address the steady slide in revenues, including by further expanding the tax base. External debt. Alongside Sri Lanka's graduation to middle-income status has come a shift away from concessional, bilateral debt and towards external debt issuance on commercial terms by state owned and commercial banks. While this is a natural progression of financial development, it also raises risks. It is essential that the proceeds of such external borrowing are invested so as to enhance productivity, add to economic resilience, and generate the foreign exchange needed to service future obligations.